Central Bank Independence and Economic Growth of Ghana: What Inflation and GDP Per Capita Growth Rates Matter? - Ding, Guoping; Vitenu-Sackey, Prince Asare (The Economics and Finance Letters, 2021)
The study analyzed data from the World Bank’s World Development Indicators, Worldwide Governance Indicators, and Heritage Foundation’s Monetary freedom index from 1996 to 2017 using the threshold regression method to determine if GDP per capita growth and inflation rates require total independence from the central bank of Ghana. From the analysis, it was observed that the impact of independence from the central bank is positively related to economic growth when the inflation threshold is less than 26.1% at a significance level of 5% with an elasticity coefficient of 0.07. On the other hand, when the inflation threshold is greater than or equal to 26.1% with an elasticity coefficient of 0.142 at a significance level of 1%, central bank independence (CBI) is positively related to economic growth. Nonetheless, the GDP per capita (PPP) growth rate witnessed a decline from 5.8% in 2017 to 4.1% in 2018 and 4.0 in 2019. The regression threshold was set at 5.8% or above to significantly impact economic growth when central bank independence is relatively improved. Furthermore, there is an inverse relationship between inflation variability, economic growth variability, and central bank independence. The responsibility of politicians is to persistently safeguard, protect and ensure the implementation of central bank independence over time.